2021
DOI: 10.1101/2021.04.01.438051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alveolar macrophages strictly rely on GM-CSF from alveolar epithelial type 2 cells before and after birth

Abstract: Programs defining tissue-resident macrophage identity depend on local environmental cues. For alveolar macrophages (AMs), these signals are provided by immune and non-immune cells, and include GM-CSF (CSF2). However, evidence to functionally link components of this intercellular crosstalk remains scarce. We thus developed new transgenic mice to profile pulmonary GM-CSF expression, which we detected in both immune cells, including group 2 innate lymphoid cells and γδ T cells, as well as AT2s. AMs were unaffecte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 84 publications
2
15
0
Order By: Relevance
“…However, despite having been reported to drive expression of EGR family members, including EGR2 (20) , in our hands, CSF-1 led to poor upregulation of EGR2 in maturing macrophages in vitro . Instead, we identified CSF-2 (GM-CSF) to be a potent inducer of EGR2 expression in maturing macrophages in vitro , a finding consistent with the almost unique dependence of alveolar macrophages on alveolar epithelial cell-derived CSF-2, and not CSF-1, for their development and survival (810) . However, TG-Fβ also induced EGR2 and we confirmed that TGF-β is indispensable for the development of alveolar macrophages (11) .…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…However, despite having been reported to drive expression of EGR family members, including EGR2 (20) , in our hands, CSF-1 led to poor upregulation of EGR2 in maturing macrophages in vitro . Instead, we identified CSF-2 (GM-CSF) to be a potent inducer of EGR2 expression in maturing macrophages in vitro , a finding consistent with the almost unique dependence of alveolar macrophages on alveolar epithelial cell-derived CSF-2, and not CSF-1, for their development and survival (810) . However, TG-Fβ also induced EGR2 and we confirmed that TGF-β is indispensable for the development of alveolar macrophages (11) .…”
Section: Discussionsupporting
confidence: 61%
“…To determine if alterations in alveolar macrophage behaviour may contribute to this, we next tested the function of Egr2 -deficient alveolar macrophages. A major homeostatic function of alveolar macrophages is the regulation of pulmonary surfactant, and the absence of alveolar macrophages results in the development of pulmonary alveolar proteinosis (PAP) (810, 27, 28) . However, Egr2 deficiency did not lead to spontaneous PAP, as there were no differences in the levels of total protein in BAL fluid from Cre + and Cre − mice at either 4 or >9 months of age, a time at which PAP is detectable in Csf2rb −/− mice (28) ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E18.5 lungs were digested and the different cell types were profiled and analyzed for Ki67 staining using flow cytometry and three comprehensive marker panels for all major lung parenchymal and mesenchymal cell compartments as well as for cells of myeloid and lymphoid lineages. 38 In the CD45compartment, Ki67 positive cells were significantly increased in Otub1 −/− parenchymal epithelial cells (EpCAM + CD31 -) and endothelial cells (CD31 + EpCAM -) as well as in Otub1 −/− mesenchymal/ other non-hematopoietic cells (EpCAM -CD31 -) compared to corresponding Otub1 +/− and Wt cell populations (Figure 5). In the endothelial cell compartment, the percentage of Ki67-positive cells was already relatively high in Otub1 +/− and Wt lungs (average of 61.2% and 66.7% per parental population), but Otub1 KO still significantly increased the percentage of Ki67-positive endothelial cells (85.3% per parental population) by around 1.3-fold (Figure 5).…”
Section: Constitutive Deletion Of Otub1 Increases the Proliferation Of All Major Lung Parenchymal And Mesenchymal Cell Typesmentioning
confidence: 93%
“…In the lower airways, alveolar macrophages (AMs) are the main immune cell type encountering airborne particles, the lungresident commensal microbiome and tasked with maintaining homeostasis (48). They actively patrol the alveoli in homeostasis and develop under the influence of epithelial-derived TGFb and GM-CSF (49)(50)(51). As such, it is not surprising that these cell types are found to behave distinctly different in the allergen- challenged lung (52).…”
Section: Acute Phase (Minutes To Hours)mentioning
confidence: 99%